Abilities of herbaceous plant species to phytoextract Cd, Pb, and Zn from arable soils after poly-metallic mining and smelting - Asare, Michael O; Pellegrini, Elisa; Száková, Jiřina; Najmanová, Jana; Tlustoš, Pavel; Contin, Marco (Environmental science and pollution research international, 2025)
Potentially toxic element (PTE) contamination deteriorates agricultural land. This study explored the accumulation of excess PTEs (Cd, Pb, and Zn) in soils by shoots of herbaceous plants growing on alluvial sediments of an abandoned mining/smelting site near the Litavka River, Czech Republic, as a means of soil remediation. Determination of total Cd, Pb, and Zn, contents in soil and plant samples decomposed with HNO3 + HCl + HF, HNO3, and H2O2, respectively, were carried out by inductively coupled optical emission spectrometry. The soil Cd, Pb, and Zn contents in the studied site ranged from 40 to 65, 3183 to 3897, and 5108 to 6553 mg kg-1, respectively, indicating serious soil contamination compared to the limits allowed by the FAO/WHO and the Czech Republic. Slightly acidic soil reactions and negative correlations between the pH, C, and N supported the assumption of relative solubility, mobility, and accumulation of studied PTEs by herbaceous species. Shoot accumulation of Cd, Pb, and Zn varied in 22 of 23 species recording a Cd content above the permissible limit. The Zn content in all plants was above the WHO limit. Except for Arabidopsis halleri, with a bioaccumulation factor (BAFshoot) > 1 for Cd and Zn, Equisetum arvense recorded a comparatively higher Cd content (10.3-28 mg kg-1) than all other species. Silene vulgaris (Moench), Leucanthemum vulgare, E. arvense, Achillea millefolium, Carex sp., Dianthus deltoides, Campanula patula, Plantago lanceolata, and Rumex acetosa accumulated more Zn than many plants (> 300 mg kg-1). Although E. arvense had a BAF < 1, it accumulated > 1000 mg Zn kg-1 and supported the phytoextraction of Zn. Only 10 species accumulated Pb above the limit permissible in plants, with L. vulgare recording the highest concentration (40 mg kg-1) among all species. Therefore, the shoots of several plant species showed promising PTE accumulation abilities and deserve more detailed studies concerning their potential use for phytoremediation of Cd-, Pb-, or Zn-contaminated soils.
Keywords: rostliny; látky znečišťující půdu; Zinc; Phytoremediation; Česká republika; olovo; Biodegradation, Environmental; biodegradace; Leucanthemum vulgare; Czech Republic; Lead; Shoot accumulation; Plants; půda; Mining; Soil Pollutants; Cadmium; Soil; hornictví; Phytoextraction; kadmium; zinek; Alluvial sediment; Equisetum arvense